IDENTIFIKASI LINGKUP ISI DAN BATAS-BATAS OTONOMI DESA PAKRAMAN DALAM HUBUNGANNYA DENGAN KEKUASAAN NEGARA - Sudantra, I Ketut (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2015)
This research objective is to study about autonomy concept in cutomary law society of desa pakraman in Bali. There are two main problems that will studied in this research, which are: (1) which powers are in scope of desa pakraman’s autonomy?; (2) what are the boundaries of desa pakraman’s autonomy in its relation with the sovereignty of  Republic of Indonesia? Based on the research’s result, can concluded that: First, it is concluded that the scope of desa pakraman’s autonomy including: (1) sovereignty to make its own law; (2) sovereignty to govern itself; (3) sovereignty to make its own self-defense force; and (4) sovereignty to perform its own court. Secondly, it is concluded that, desa pakraman’s autonomy isn’t a autonomy without boundary, it is bound by conditions set by state’s constitution, which is must on date and principles of Republic of Indonesia.
Keywords: customary law society; desa pakraman; autonomy